PROBLEMS AND STRATEGIES IN TEACHING PRONUNCIATION ON ENGLISH DEPARTMENT STUDENTS - Yousef Bani Ahmad (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2019)
This study attempts to investigate the problems and strategies in solving incorrect pronunciation on English education students. The research used descriptive method. The subjects of this research were 6 students, department of English education. The technique of the data collection were a test recording and interview. Test was used to understand the students problems and interview was conducted to re-check the information and data obtained. Results showed English pronunciation problems were caused by the difference of language system between English and Bahasa, students had a lack of mastery of consonant and vowel in accordance with international Phonetics alphabet, the incompatibility of the placement place and manner of articulation. Strategies to overcome the problems of English pronunciation learning by using audio-visual media, the lecturer gave oral corrective feedback for those students who got the errors in pronunciation, students used the mobile phone application in supporting individually pronunciation learning and students had a lot of practicing in reading english texts were provided by lecturer.